HUBUNGAN POSTUR KERJA, DURASI MENGEMUDI DENGAN KELUHAN NYERI PUNGGUNG BAWAH (NPB) PADA SOPIR TRUK BARANG ANTAR KOTA DI CV SEMERU PUTRA SEMARANG - Naufal Afif; Siswi Jayanti; Ida Wahyuni (Jurnal Kesehatan Masyarakat (Undip), 2021)
Low Back Pain (LBP) is a painful sensation that is felt on the back, muscles, nerves, lower ribs number 12 to the inner end of the buttock folds, and can be accompanied by spreading pain in the legs. Being a truck driver runs the risk of muscle disorders that can lead to LBP. The causative factors come from personal factors, which are age, years of service, and body mass index. And working factors as well, which are driving duration and work posture. From the results of interviews, many truck drivers complained about pain in the lower back. Purpose of this study is to analyze the correlation between individual factors, sitting posture, and driving duration with complaints of low back pain (LBP) in truck driver CV Semeru Putra Semarang. Methods of this research is using an explanatory research and cross sectional approach. For the sampling, the Lemeshow formula is used in order to get 46 truck drivers and done online using the google form. This research instrument is a questionnaire, using the BRIEF Survey to measure working posture for back, a VAS sheet (Visual analoque scale) to describe subjective pain complaints and posture photos while driving. The results showed that the truck drivers complained about LBP in the light category 76,1%, and 23.9% heavy. From the results statistic test of the chi-square analysis, it was found that there was a significant relationship between LBP complaints in truck drivers with body mass index (α = 0.013) and driving duration (α = 0.047). Meanwhile, those that were not related were years of service (α = 0.447), back work posture (α =0.474), and age (α =0.247). Suggestions for truck drivers to lose weight, stretch, do routine engine maintenance and rest when tired.